Analisis Pendapatan Usaha Industri Rumah Tangga Amplang Ikan Tenggiri (Scomberomorus commerson) Di Desa Tabanio Kecamatan Takisung Kabupaten Tanah Laut (Studi Kasus Amplang Ikan Tenggiri Mama Helman) - Aldi Anjayani; Ari Jumadi Kirnadi; Yarna Hasiani (Fakultas Pertanian UVAYA Banjarmasin, 2023)
This was carried out in Tabanio Village, Takisung District, Tanah Laut Regency. The method used in this research is the case study method in industrial enterprises Mama Helman's mackerel fish amplang household in Tabanio Village, District Takisung, Tanah Laut Regency. The results of this study indicate that the stages making mackerel fish amplang which includes, preparation of tools and materials, weeding, washing, taking meat, pulverizing meat, mixing, forming dough, frying, draining and packaging. The amount of the fee is Rp 44,896,592/month, revenue of IDR 57,600,000/month, income of IDR 13,563,408/month, a profit of IDR 12,703,408/month, an RCR value of 1.3 and The problems faced in making mackerel fish shells are raw materials in the form of mackerel when the weather is bad like the wind is always strong so that the fishermen can not catch fish in the sea this causes the high price of staple raw materials in the form of mackerel